Leader interpersonal and influence skills : the soft skills of leadership - Riggio, Ronald E.; Tan, Sherylle J. (New York : Routledge, Taylor & Francis Group, 2014)
"This edited volume explores different models, conceptualizations, and measures of leader interpersonal and influence "soft skills" that are so necessary for effective leadership. These include the communication skills, persuasion skills, political savvy, and emotional abilities used by leaders to inspire, motivate, and move followers toward the accomplishment of goals. The book emanates from the two-day-long 21st Kravis-de Roulet leadership conference, which brought together top scholars working in this area. The intent of the conference and this edited volume is to increase understanding of the interpersonal and influence skills, or "soft skills," of the leader, to highlight state-of-the-art research on the topic, and to provide clear, research-based guidelines for the development of leader skills. Chapter authors are recognized experts in their respective areas, and each section of the book will be introduced by an editor-authored chapter reviewing the specific topic area in brief"--
"This edited volume explores different models, conceptualizations, and measures of leader interpersonal and influence "soft skills" that are so necessary for effective leadership. These include the communication skills, persuasion skills, political savvy, and emotional abilities used by leaders to inspire, motivate, and move followers toward the accomplishment of goals"--
ch. 1. The "hard" science of studying and developing leader "soft" skills / Ronald E. Riggio -- Part I. Foundational models for leader interpersonal skills and competencies -- ch. 2. Toward the development of a model and a measure of managerial interpersonal skills / Shaun Pichler and Gerard Beenan -- ch. 3. A social skills model for understanding the foundations of leader communication / Ronald E. Riggio -- Part II. Leader emotional competencies -- ch. 4. Using a multilevel theory of performance based on emotional intelligence to conceptualize and develop "soft" leader skills / Cary Cherniss and Richard E. Boyatzis -- ch. 5. The role of nonverbal behavior in leadership : an integrative review / Annick Darioly and Marianne Schmid Mast -- ch. 6. A conceptual framework of emotion management in leadership contexts / Shane Connelly [and others] -- Part III. Influence and political skills of the leader -- ch. 7. Leader ethos : how character ontributes to the social influence of the leader / Peter L. Jennings and Sean T. Hannah -- ch. 8. Leader political skill and team effectiveness : the positioning of poitical skill in the framework of leader competencies / Darren C. Treadway [and others] -- ch. 9. Social identity framing : a strategy of social influence for social change / Viviane Seyranian -- Part IV. Implementing and developing leader interpersonal and influence skills -- ch. 10. Leveraging the science of memory to enhance the efficacy of leader communications / Jay A. Conger -- ch. 11. Developing capacity for responsible leadership : the interactive role of identity and competence development / Craig R. Seal [and others] -- ch. 12. Soft skills training : best practices in industry and higher education / Susan Elaine Murphy, Stefanie P utter, and Stefanie K. Johnson -- ch. 13. Developing emotional, social, and cognitive competencies in MBA programs : a twenty-five year perspective / Richard E. Boyatzis, Angela Passarelli, and Hongguo Wei.
Includes bibliographical references and index.
Keywords: Leadership -- Psychological aspects